2021
DOI: 10.1080/26410397.2021.1892570
|View full text |Cite
|
Sign up to set email alerts
|

Can changes to improve person-centred maternity care be spread across public health facilities in Uttar Pradesh, India?

Abstract: Green (2021) Can changes to improve person-centred maternity care be spread across public health facilities in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
0
3
0
2
Order By: Relevance
“…Very few comparative studies measured the effect of interventions to improve RMC and showed divergent results 11 17 36. Some authors attribute this to the multiple and complex challenges of implementing change in a low-resource setting and variations in measurement 9 17. The study that obtained similar results to ours is the one that implemented a complex strategy, which was designed in a participatory manner with multiple stakeholders and levels of leadership, specific to the context and supported structural improvements 11.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Very few comparative studies measured the effect of interventions to improve RMC and showed divergent results 11 17 36. Some authors attribute this to the multiple and complex challenges of implementing change in a low-resource setting and variations in measurement 9 17. The study that obtained similar results to ours is the one that implemented a complex strategy, which was designed in a participatory manner with multiple stakeholders and levels of leadership, specific to the context and supported structural improvements 11.…”
Section: Discussionmentioning
confidence: 56%
“…Either way, uncontrolled pre–post intervention studies fail to identify whether the improvements are associated with the intervention or secular trends. Very few comparative studies measured the effect of interventions to improve RMC and showed divergent results 11 17 36. Some authors attribute this to the multiple and complex challenges of implementing change in a low-resource setting and variations in measurement 9 17.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…La atención de maternidad de mala calidad conduce a retrasos en la atención y resultados adversos para la gestante y el recién nacido, incluida la mortalidad perinatal. Un estudio cuasi experimental en India demostró que la ACP mejoró los resultados (52) .…”
Section: Atención Obstétrica Centrada En La Mujerunclassified
“…• Cambiar el paradigma en las políticas de salud, fortalecer el primer nivel de atención para rescatar la atención primaria conforme las conclusiones de Alma Ata y prestar atención centrada en la persona (52,(65)(66)(67)(68) • Mejorar la planta física y el equipamiento de los establecimientos de salud para atender adecuada, oportuna y dignamente a las gestantes, parturientas y recién nacidos (9,21,49) • Construir un sistema de salud integral, con dimensiones biopsicosociales, culturales, espirituales y energéticas debidamente armonizadas y equilibradas, basadas en el derecho a la salud y con la participación intersectorial de todo el Estado, construyendo la defensa de la salud de las personas, la familia y la comunidad (13,19) • Educar al personal de salud y formar tutores en medicina centrada en las personas desde el pregrado, el posgrado y en la educación médica continua, de manera de fortalecer las actitudes (9,19,32,35,56,69,70,71) • Construir una salud participativa y consensuada, entre cuidadores y cuidados, con respeto irrestricto a las ideas de todos (18) • Utilizar la medicina basada en evidencias para fortalecer la MCP (14,20,30,39,72) • Fomentar la investigación de la atención obstétrica centrada en la persona (7,14,18) • Fortalecer la participación familiar y comunitaria en el cuidado de las personas (4,12,65) • Actualizar las Guías Nacionales de Atención Integral de la Salud Sexual y Reproductiva (53,54) .…”
Section: Recomendacionesunclassified